Characterization and Preparation of Nano-porous Carbon Derived from Hemp Stems as Anode for Lithium-Ion Batteries - Guan, Zhongxiang; Guan, Zhiping; Li, Zhigang; Liu, Junhui; Yu, Kaifeng (Nanoscale research letters, 2019)
As a biomass waste, hemp stems have the advantages of low cost and abundance, and it is regarded as a promising anode material with a high specific capacity. In this paper, activated carbon derived from hemp stems is prepared by low-temperature carbonization and high-temperature activation. The results of characterizations show the activated carbon has more pores due to the advantages of natural porous structure of hemp stem. The aperture size is mainly microporous, and there are mesopores and macropores in the porous carbon. The porous carbon has an excellent reversible capacity of 495 mAh/g after 100 cycles at 0.2 °C as the anode of lithium-ion battery. Compared with the graphite electrode, the electrochemical property of activated carbon is significantly improved due to the reasonable distribution of pore size. The preparation of the activated carbon provides a new idea for low cost and rapid preparation of anode materials for high capacity lithium-ion batteries.